Dark life - Falls, Kat. (Scholastic Press, 2010)
When fifteen-year-old Ty, who has always lived on the ocean floor, joins Topside girl Gemma in the frontier's underworld to seek and stop outlaws who threaten his home, they learn that the government may pose an even greater threat.